2001
DOI: 10.1074/jbc.m104934200
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Cardiac Changes and Premature Death in Transgenic Mice Overexpressing a Mutant Form of Serum Response Factor

Abstract: Serum response factor (SRF) is a key regulator of a number of extracellular signal-regulated genes important for cell growth and differentiation. A form of the SRF gene with a double mutation (dmSRF) was generated. This mutation reduced the binding activity of SRF protein to the serum response element and reduced the capability of SRF to activate the atrial natriuretic factor promoter that contains the serum response element. Cardiac-specific overexpression of dmSRF attenuated the total SRF binding activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…The apparent block to myofiber growth after skeletal muscle deletion of Srf is reminiscent of the cardiac phenotype resulting from cardiac expression of dominant negative SRF (39) or cardiac deletion of Srf, which results in embryonic lethality from a defect in ventricular growth and maturation (27,28). Conversely, overexpression of SRF results in lethal cardiomyopathy with associated myocyte hypertrophy in adult cardiac muscle (40).…”
Section: Control Of Myofiber Growth and Maturation By Srfmentioning
confidence: 99%
“…The apparent block to myofiber growth after skeletal muscle deletion of Srf is reminiscent of the cardiac phenotype resulting from cardiac expression of dominant negative SRF (39) or cardiac deletion of Srf, which results in embryonic lethality from a defect in ventricular growth and maturation (27,28). Conversely, overexpression of SRF results in lethal cardiomyopathy with associated myocyte hypertrophy in adult cardiac muscle (40).…”
Section: Control Of Myofiber Growth and Maturation By Srfmentioning
confidence: 99%
“…In contrast to the above instances, much in vivo genetic evidence exists for SRF playing a critical role in processes unrelated to cell replication. For example, cardiac-restricted overexpression of either wild-type or dominant-negative SRF results in various forms of heart failure because of severe alterations in contractile gene expression (125,126). Moreover, SRF inactivation or knockdown in D. discoideum (26), Drosophila melanogaster (91), Caenorhabditis elegans (30), and Mus musculus (1,28,55,61,70,78,81,82) does not result in impaired cell proliferation.…”
Section: Serum Response Factor: Toggle Switch For Disparate Programs mentioning
confidence: 99%
“…a) SRF is significantly up-regulated in PTC and anaplastic carcinoma as compared to SRF expression in follicular SRF plays a key role in many cellular processes, including cell cycle regulation, apoptosis, cell growth and differentiation and cell-specific gene regulation (3)(4)(5)(6)(7)(8)(9)(10). Accumulating evidence has suggested that SRF plays multiple roles in carcinogenesis and cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, DNA binding sites for SRFs (serum response elements-SREs) have been found in the promoters of ~50 different genes, including immediateearly genes such as c-fos and Egr-1 (3)(4)(5). Studies have also shown that SRF is involved in various cellular processes such as expression of immediate-early and tissue-specific genes, cell proliferation, differentiation and apoptosis (6)(7)(8)(9)(10). A previous study has demonstrated that SRF plays a role in tumor progression, specifically in the mesenchymal transition of epithelial tumor cells (11).…”
Section: Introductionmentioning
confidence: 99%